EFEKTIVITAS PENAGIHAN TUNGGAKAN PAJAK KENDARAAN BERMOTOR DALAM RANGKA MENINGKATKAN PENERIMAAN PADA SAMSAT JAKARTA UTARA - Harjo, Dwikora; Putri, Elvani (Jurnal Ilmu Administrasi Publik, 2025)
The background of this research is the unachieved target in revenue and the increase in arrears at the North Jakarta Samsat in 2021-2023. The purpose of this study is to analyze the effectiveness of billing as well as the obstacles and efforts made at the North Jakarta Samsat. The method used in this research is a descriptive qualitative research method. Data collection carried out in this study is by means of interviews, observation and documentation. The theory used is the theory put forward by Harrington Emerson (Handayaningrat, 2017) with 2 dimensions, namely the achievement of goals, and time standards. The results showed that the effectiveness of motor vehicle tax collection in North Jakarta Samsat was not effective as seen from the increase in arrears and realization that had not been achieved. Problems arising from the lack of optimal collection due to lack of socialization, inadequate human resources, low economic capacity and facilities and infrastructure that are not optimal. facilities and infrastructure that are not optimal